Levels of Music Played by Caucasian and Filipino Musicians with and without Conventional and Musicians’ Earplugs - Rawool, Vishakha; Buñag, Roraine (Journal of the American Academy of Audiology, 2019)
Some musicians may play the music louder while using earplugs thus reducing the effectiveness of the hearing protection offered by earplugs. In addition, the dynamic range (DR) of the music may be altered because of the use of earplugs with negative impact on perceived quality of music. There are some cultural differences in attitudes toward loudness, which may lead to differences in the loudness of music played by musicians from different cultures.To investigate the effect of the use of two different types of earplugs on the loudness and DR of music played by musicians of Caucasian and Filipino origins.Quasi-experimental repeated measures design.Thirty six musicians with normal hearing within the age range of 18–49 yr. Fifteen were of Caucasian (eight men and 7 women) origin and 21 were of the Filipino (nine men and 12 women) origin.All participants received a brief educational session, which included information on music-induced hearing loss, the benefit of using earplugs, and the correct procedures for inserting and removing earplugs. They played music in five different conditions (three min each): Trial 1 of conventional and musicians’ earplugs in random order, no earplug, and trial 2 of conventional and musicians’ earplugs in random order.Maximum, minimum, average (average sound level measured over the measurement period; LAVG), and peak levels were recorded using a dosimeter while playing music in each of the five conditions. The DR was derived by subtracting the minimum values from the maximum values. A different measure of the dynamic range 2 (DR2) was derived by subtracting the LAVG value from the peak value. Mixed analyses of variance (ANOVA) (Cultural origin and Gender as nonrepeated variables) was performed on LAVG, DR, and DR2.Based on the LAVG levels yielded by them, 42–61% of the musicians may be at risk for hearing loss. The mixed ANOVA revealed some main effects of culture and some significant interactions involving cultural origin, the plug conditions, type of earplugs, and trial number.Use of earplugs may vary the overall loudness of music, the DR, or the DR2 in some musicians depending on the type of earplugs and cultural origin, and the effect may change with practice.
Keywords: Caucasian; culture; earplugs; Filipino; hearing protection devices; loud music; musician